Direct catalytic upgrading of biomass pyrolysis vapors by a dual function Ru/TiO2 catalyst. Issue 7 (22nd February 2013) - Wan, Shaolong; Pham, Trung; Zhang, Sarah; Lobban, Lance; Resasco, Daniel; Mallinson, Richard
<x xml:space="preserve">Abstract</x> The results of catalytic treatment of vapors exiting a g/min pyrolysis unit before product condensation to the liquid phase using a Ru/TiO2 catalyst for oak and switchgrass pyrolysis are reported. The pyrolysis is conducted at 500°C and the catalysis at 400°C at atmospheric pressure with a hydrogen partial pressure of 0.58 atm. It is found that the catalytic treatment provides significant conversion of light oxygenates to larger, less oxygenated, molecules and, simultaneously, bio‐oil phenolics are also converted to less oxygenated phenolics with methoxy methyl groups transferred to the ring. The activity of the catalyst gradually diminished with increasing biomass fed to the system. Untreated pyrolysis oil forms a single liquid phase with some tarry material, consistent with the literature, whereas the treated liquid product forms separate oil and aqueous phases, the latter of which is about 80% water. The oil from the treated vapors has a lower initial viscosity with only a small increase upon accelerated aging compared to the untreated product oil, which has a dramatic increase in viscosity after aging. This is indicative of poor oil stability for untreated oil that is further confirmed by large increases in molecular weight, while the treated oil has a small increase in molecular weight after accelerated aging. In an effort to understand compatibility with refinery streams, the solubility of the oils in tetralin was examined. The untreated oil was found to have very limited solubility in tetralin, whereas the treated oil phase was completely soluble except for a small aqueous phase that appeared. There are a number of challenges in developing a high yield process for pyrolysis based conversion of biomass to transportation fuels. The Ru/TiO2 catalyst used here shows promise for conducting multiple types of favorable reactions in the presence of the full spectrum of primary pyrolysis products that creates significant product stability under mild conditions. This could lead to higher liquid yields of stable, refinery compatible, product oil. © 2013 American Institute of Chemical Engineers AIChE J, 59: 2275–2285, 2013